2021
DOI: 10.1021/acsomega.1c03318
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Van der Waals Interactions in Hydrogen Adsorption on a Silicon-carbide Nanotube Revisited with vdW-DFT and Quantum Monte Carlo

Abstract: Density functional theory (DFT) is a valuable tool for calculating adsorption energies toward designing materials for hydrogen storage. However, dispersion forces being absent from the local/semi-local theory, it remains unclear as to how the consideration of van der Waals (vdW) interactions affects such calculations. For the first time, we applied diffusion Monte Carlo (DMC) to evaluate the adsorption characteristics of a hydrogen molecule on a (5,5) armchair silicon-carbide nanotube (H2-SiCNT). Within the DF… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 55 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Even though the analytical interaction energies fall in the desired range (∼15–48 kJ mol −1 ), 26 both isosteric heat of adsorption and first-principles binding energy calculations show low values (physisorption) between one gaseous H 2 molecule and all 5 studied terminated planes of MgB 2 . Considering these results in light of the high storage capacity that was experimentally witnessed on MgB 2 , we lean towards the postulate that H 2 dissociates subsequent to adsorption, followed by H atoms’ diffusion into the crystal lattice.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Even though the analytical interaction energies fall in the desired range (∼15–48 kJ mol −1 ), 26 both isosteric heat of adsorption and first-principles binding energy calculations show low values (physisorption) between one gaseous H 2 molecule and all 5 studied terminated planes of MgB 2 . Considering these results in light of the high storage capacity that was experimentally witnessed on MgB 2 , we lean towards the postulate that H 2 dissociates subsequent to adsorption, followed by H atoms’ diffusion into the crystal lattice.…”
Section: Resultsmentioning
confidence: 92%
“…The focus on MgB 2 /Mg(BH) 4 as well as borohydrides for hydrogen storage has been discussed elsewhere with the key advantage being the potential for high gravimetric and volumetric storage densities as noted above. 6,[21][22][23][24][25] For hydrogen storage purposes, the interaction between hydrogen and an ideal sorbent material can be intuitively understood to have an optimal range (reportedly B15-48 kJ mol À1 by Prayogo et al), 26 where it is larger than physical adsorption for better retention at room temperature and smaller than chemisorption in order to allow low energy desorption. 27 A study from Ray et al in 2017 showed direct hydrogenation from MgB 2 to Mg(BH) 4 , which went through two steps: (1) dissociation of the H 2 molecule and (2) diffusive absorption initially from the high energy B-B bond.…”
Section: Introductionmentioning
confidence: 99%
“…Since van der Waals interactions affect distribution of electronic density, 45) the differences of approximation were investigated using the unit cells in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Diffusion Monte Carlo (DMC), a real-space, ground-state QMC method, has long been viewed as the gold standard for modeling the ground state properties of correlated solids due to its ability to accurately describe electron correlation. Previous work has established QMC as a highly accurate method for describing the properties of correlated solids, including transition metal oxides and doped and/or defective materials. More recent studies have demonstrated similar accuracies for covalent solids, especially materials involving van der Waals interactions, encouraging DMC’s use in problems that require precise energy calculations, including heterogeneous catalysis. Furthermore, DMC has a comparatively low, polynomial ( O ( N 3 – N 4 ), where N is the number of electrons) cost compared to coupled cluster theory (CCSD­(T))- and full configuration interaction (FCI)-based methods. ,, …”
Section: Introductionmentioning
confidence: 99%